2016
DOI: 10.3758/s13428-016-0835-9
|View full text |Cite
|
Sign up to set email alerts
|

Is pupillary response a reliable index of word recognition? Evidence from a delayed lexical decision task

Abstract: Previous word recognition studies have shown that the pupillary response is sensitive to a word's frequency. However, such a pupillary effect may be due to the process of executing a response, instead of being an index of word processing. With the aim of exploring this possibility, we recorded the pupillary responses in two experiments involving a lexical decision task (LDT). In the first experiment, participants completed a standard LDT, whereas in the second they performed a delayed LDT. The delay in the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 25 publications
2
22
1
Order By: Relevance
“…First, there is a question of whether the pupil can respond to the sentiment of a word before the gaze is transferred to the next one. Classic studies reported pupil latencies under 300 ms in cognitive tasks (Ahern & Beatty, 1979), whereas recent experiments in reading and lexical decision tasks demonstrated that the peak pupil latency can be significantly higher (note, however, that this may be due to the need to execute a response after each word, unlike in our study; see, e.g., Haro, Guasch, Vallès, & Ferré, 2017). On the one hand, approximately half of the looking durations that we registered were below 300 ms. On the other hand, it appears that the number of long fixations was sufficiently large to allow for significant pupil dilation results despite the noise brought about by the uninformative short fixations.…”
Section: Discussioncontrasting
confidence: 87%
“…First, there is a question of whether the pupil can respond to the sentiment of a word before the gaze is transferred to the next one. Classic studies reported pupil latencies under 300 ms in cognitive tasks (Ahern & Beatty, 1979), whereas recent experiments in reading and lexical decision tasks demonstrated that the peak pupil latency can be significantly higher (note, however, that this may be due to the need to execute a response after each word, unlike in our study; see, e.g., Haro, Guasch, Vallès, & Ferré, 2017). On the one hand, approximately half of the looking durations that we registered were below 300 ms. On the other hand, it appears that the number of long fixations was sufficiently large to allow for significant pupil dilation results despite the noise brought about by the uninformative short fixations.…”
Section: Discussioncontrasting
confidence: 87%
“…The items were presented for 600 ms, with a crosshair (“+”) in the interstimulus interval (1400 ms), in random order. This is a slight modification of a standard lexical decision task, which typically contrasts existing words with unknown pseudowords (e.g., [ 40 , 41 ]), whereas here we used newly learned words as critical stimuli. In the free-form definition task, participants were presented with 20 newly learnt words that they had to define by typing their definitions into the spreadsheet.…”
Section: Methodsmentioning
confidence: 99%
“…Research examining the task‐evoked pupillary response (TEPR) provides evidence that the relationship between pitch accenting and referent status affects comprehenders' cognitive load during spoken discourse processing. Generally, smaller pupillary responses are observed when language processing is facilitated by intrinsic characteristics of the linguistic input such as speech quality (Koch & Janse, 2016; Kuchinsky et al, 2013; McGarrigle, Dawes, Stewart, Kuchinsky, & Munro, 2017; Tamási, McKean, Gafos, Fritzsche, & Höhle, 2017; Wagner, Toffanin, & Başkent, 2016; Winn, Edwards, & Litovsky, 2015; Zekveld, Kramer, & Festen, 2010), lexical characteristics (Chapman & Hallowell, 2015; Frank & Thompson, 2012; Geller, Landrigan, & Mirman, 2019; Geller, Still, & Morris, 2016; Guasch, Ferre, & Haro, 2017; Haro, Guasch, Vallès, & Ferré, 2017; Hyönä, Tommola, & Alaja, 1995; Kuchinke, Võ, Hofmann, & Jacobs, 2007; Ledoux et al, 2016; Lõo, van Rij, Järvikivi, & Baayen, 2016; Papesh & Goldinger, 2012), lack of syntactic ambiguity (Ben‐Nun, 1986; Just & Carpenter, 1993; Nikuni, Yasunaga, Iwasaki, & Muramoto, 2015; Sauppe, 2017; Schluroff, 1982; Sevilla, Maldonado, & Shalóm, 2014), and discursive implications (Demberg & Sayeed, 2016; Tromp, Hagoort, & Meyer, 2016). Conversely, larger pupillary responses are observed when language must be comprehended while simultaneously performing other tasks (Causse, Peysakhovich, & Fabre, 2016; Demberg & Sayeed, 2016; Koelewijn, de Kluiver, Shinn‐Cunningham, Zekveld, & Kramer, 2015; Koelewijn, Shinn‐Cunningham, Zekveld, & Kramer, 2014; Kramer et al, 2013) as well when language comprehension is difficult due to conditions such as aphasia and cognitive aging (Chapman & Hallowell, 2015; Hochmann & Papeo, 2014; Koch & Janse, 2016; Piquado, Isaacowitz, & Wingfield, 2010; Schmidtke, 2014; Wendt, Dau, & Hjortkjær, 2016; see Schmidtke, 2018, for a review), indicating that task‐external factors also affect pupillary responses during language comprehens...…”
Section: Introductionmentioning
confidence: 99%